Critical soft factors for card-based production systems implementation: A multi-method study - Bagni, Gustavo; Godinho Filho, Moacir; Tortorella, Guilherme Luiz; Jabbour, Charbel José Chiappetta (Brazilian Journal of Operations & Production Management, 2021)
Goal: Although card-based systems are a mature topic in literature, studies have focused mainly on how to optimize parameter of each system. The influential of human factors in the implementation of those systems have rarely been evaluated. Therefore, this study aims to understand what are the critical soft factors for a successful card-based systems implementation. Design / Methodology / Approach: A multi-method study is used in this research, combining systematic literature review, longitudinal case study, content analysis, interviews with experts and validations with two different groups. Results: The paper proposes a list of 15 soft factors critical to a successful implementation of card-based systems categorized in a “house framework” according to the level of analysis each factor is included. Limitations of the investigation: A single case study, although longitudinal, was conducted to proposed the list of factors. Therefore, further studies should be conducted to adapt the list to other organizations and contexts. Practical implications: Following the proposed list of factors, managers can increase the success in implementing a card-based system in their organizations. Originality / Value: This study combines different research methods in a unique way, since in the researchers' view, an individual method was not sufficient to answer the proposed research question. Moreover, the case study reported a failure implementation of a card-based system, a rare addition to literature which mainly presented success cases.